Muscular and non-muscular contributions to maximum power cycling in children and adults: implications for developmental motor control - Korff, T.; Hunter, E. L.; Martin, J. C. (The Journal of Experimental Biology, 2009)
During submaximal cycling, children demonstrate a different distribution between muscular and non-muscular (gravitational and motion-dependent) forces when compared with adults. This is partly due to anthropometric differences. In this study, we tested the hypothesis that during maximum power cycling, children would construct the task (in terms of the distribution between muscular and non-muscular pedal power) similarly to adults. Eleven children (aged 8-9 years) and 13 adults (aged 20-40 years) performed a maximal isokinetic cycling task over 3 s at 115 r.p.m. Multivariate analyses of variance revealed no significant differences in normalized maximum, minimum and average positive non-muscular pedal power between children and adults (Wilks' =0.755, F3,20=2.17, P=0.124). Thus, maximum cycling is a developmental `self-scaling' task and age-related differences in muscular power production are not confounded by differences in anthropometry. This information is useful to researchers who wish to differentiate between muscular and non-muscular power when studying developmental motor control. In addition to the similarities in the distribution between muscular and non-muscular pedal power, we found age-related differences in the relative joint power contributions to total pedal power. In children, a significantly smaller proportion of total pedal power was generated at the ankle joint (6.1±5.4% for children and 12.6±3.2% for adults), whilst relatively more power was generated at the knee and hip joints. These results suggest that intermuscular coordination may be contributing to children's limits in maximum power production during multi-joint tasks.